SOCIOECONOMIC IMPACT OF MOTORCYCLE ACCIDENT VICTIMS IN THE EMERGENCY ROOM OF A HOSPITAL (PART 2) - BITTAR, CINTIA KELLY (Acta Ortop Bras, 2020)
OBJECTIVE: To evaluate the socioeconomic impact of motorcycle accidents of a metropolis with one million inhabitants treated by a university hospital in 2017. To study hospital cost and time of victims, evaluate definite and incapacitating sequelae, and analyze patient’s insertion in the labor market six months after the accident. METHODS: Retrospective study of 62 victims of motorcycle accidents treated in the emergency room and referred for surgical procedure in a university hospital. Data were collected from medical records and answers via telephone six months after the trauma. RESULTS: Injuries related to motorcycle accident resulted in high hospital costs. Average loss per patient was R$ 17,555. Of those who answered the functional impact questionnaire, 64% were on paid leave by INSS and 84% presented partial or permanent physical disabilities after the accident. Only 9 people (36%) received any kind of financial benefit from public authorities. CONCLUSION: High costs are directly related to hospitalization time and surgical needs. Most victims needed financial help and had their social lives aggravated. Investments in motorcyclists’ awareness of traffic laws and use of safety equipment are needed, as well as in road infrastructure. Level of evidence II, Prognostic studies.